Pendampingan Pengendalian Semut Hitam (Dolichoderus Thoracicus) pada Buah Kopi di Kelompok Tani Kopi Desa Curahpoh, Curahdami, Bondowoso - Distiana Wulanjari; Muhammad Ghufron Rosyady; Oria Alit Farisi; Muhammad Burhanuddin Irsyadi (Universitas 45 Surabaya, 2025)
Curahpoh is one of the villages in Bondowoso regency that is one of the growing coffee centers. During the coffee harvest season, farmers experience difficulties harvesting coffee cherries due to the large number of black ants that nest in the coffee cherries. This results in a decrease in coffee production and harvesting is not maximized. So, efforts need to be made to optimize the harvest of coffee fruit. This community service aims to control black ants on coffee fruit in farmer groups in Curahpoh village, Curahdami, Bondowoso. This community service was carried out in several stages, namely field surveys, socialization of plant pest organisms and natural predators, control practices and monitoring. The results of this community service obtained that black ants act as natural predators of mealybugs on coffee fruit cups. Coffee farmers were enthusiastic during the socialization and assistance in the practice of making artificial ant nests that were hung on coffee plants. The black ants move from the coffee pods into the artificial nest, so that the coffee fruit harvesting process can be carried out optimally.